Kinetic, Isotherm and Thermodynamic Studies on the Removal of Zn (II) From Aqueous Solution using Silica Adsorbent - Vivekanand Choudhary; Twinkle Keshari; Himanshu Shekhar (Journal of Advances in Environmental Health Research)
Background: Water is essential for all life, but pollution, including heavy metals, poses severe health risks. The adsorption technology, known for being safe, cost-effective, and eco-friendly, uses silica to remove zinc ions from water. This paper detailed the kinetics, isotherms, and thermodynamics of this process.Methods: A stock solution of zinc sulfate in distilled water was prepared. Silica oxide, with its high surface area, was used to remove zinc ions from solutions of 5, 10, 15, and 20 mg/L concentrations. A double beam atomic absorption spectrophotometer (AAS) was used to obtain the calibration curve for the experiments. Results: The study investigated the removal efficiency of Zn (II) using SiO₂ as an adsorbent. Factors such as initial concentration, contact time, adsorbent dose, pH, agitation speed, and temperature were examined in a batch process. Equilibrium was reached in 60 minutes for all concentrations.Conclusion: The highest Zn (II) adsorption (88%) was achieved with a 10 mg/L solution at pH 6, 180 rpm, and 303 K, using 1 g/L of silica. The adsorption kinetics followed a first-order rate mechanism with a rate constant of 3.91 × 10⁻² 1/min at 30 °C. Both Langmuir and Freundlich isotherms fit the data well, with rate constants of 0.089 and 0.248, respectively. The maximum adsorption capacity (qmax) from the Langmuir isotherm was 0.9416. The negative free energy change (ΔG° = -3938.21 kJ/mol at 298 K) indicated high capacity and affinity for Zn (II) removal, confirming the process’s feasibility and spontaneity.